Aspects of intercommunity population balance in Northern Ireland - Compton, P.A; Boal, F.W. (Economic & Social Studies, 1970)
The population of Northern Ireland is probably unique in that it is composed of two groups of people each of which can be characterized as a 'minority'. Conventional wisdom has it that at present there is a dominant Protestant majority wishing to maintain political links with Great Britain, and a Catholic minority desirous of closer links with, i f not absorption by, the Irish Republic. The seeming paradox of two minorities is explained, on the one hand, by the existence of the current Catholic minority; and, on the other, by a Protestant group, in the majority at present, fearing that in time it will become a minority. As the recent Commission on Disturbances in Northern Ireland said '. . . among Protestants there are deep-rooted suspicions and fears of political and economic domination by a future Catholic majority in the population'. This fear is partly caused by the knowledge that the average size of Catholic families is significantly larger than average non-Catholic families. Out of this situation has sprung rumour and counter-rumour concerning the precise current population balance between the two communities.
Keywords: Demographics; Northern Ireland